Analisis Harmonik Beban Lampu LED Taxiway Light - Desriyanto, Nurhedhi; ISMAIL, KGS; Samanhudi, Asep (Jurnal Sains dan Teknologi Penerbangan, 2024)
Harmonics are a phenomenon that arises due to the use of non-linear loads in electric power systems. Harmonic problems in electric power systems are increasingly complex with the increasing use of non-linear equipment (for example: LED lights). In this research, harmonic measurements were carried out using a Power Analyzer measuring instrument. Measurements were taken for the Taxiway Light load on the South Runway at Soekarno Hatta Airport which uses LED lights. The measurement results show that high harmonic currents are still visible, exceeding the standard value of short circuit ratio for electrical installations of 15%. The largest harmonic currents are detected in the 3rd order with a frequency of 150 Hz (3 x 50 Hz). The percentage of current harmonics in the 3rd order reaches 108.02%, while the voltage harmonics have almost the same spectrum characteristics and occur in the odd order. The most significant voltage harmonics were detected in the 5th order, namely 5 x 50 Hz = 250 Hz with an average percentage of harmonic voltage at this frequency of 1.54%.